2020
DOI: 10.1136/bmjopen-2020-039159
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of remdesivir in patients with COVID-19: a protocol for systematic review and meta-analysis of randomised controlled trials

Abstract: BackgroundDespite global containment measures to fight the coronavirus disease 2019 (COVID-19), the pandemic continued to rise, rapidly spread across the world, and resulting in 2.6 million confirmed cases and 185 061 deaths worldwide as of 23 April 2020. Yet, there are no approved vaccines or drugs to make the disease less deadly, while efforts are underway. Remdesivir, a nucleotide-analogue antiviral drug developed for Ebola, is determined to prevent and stop infections with COVID-19, while results are yet c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Remdesivir significantly shortened recovery time to 11 days versus 15 days of placebo, decreased mortality rate in 14 days to 7.1% compared with 11.9% of placebo administration, and lower adverse events of 21.1% versus 27% [ 50 ]. An ongoing systematic review of randomized controlled trials on efficacy of Remdesivir in COVID-19 patients will provide us with more features of the treatment effect of this drug [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Remdesivir significantly shortened recovery time to 11 days versus 15 days of placebo, decreased mortality rate in 14 days to 7.1% compared with 11.9% of placebo administration, and lower adverse events of 21.1% versus 27% [ 50 ]. An ongoing systematic review of randomized controlled trials on efficacy of Remdesivir in COVID-19 patients will provide us with more features of the treatment effect of this drug [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…So far, in secondary prevention, there is no effective anti-SARS-COV-2–specific viral agent. Available antiviral medication like remdesivir which shortened hospital stay and significantly lowered mortality rate [ 51 ] associated with supportive cares for each COVID-19 cases has been used. A systematic review reported the superiority of nucleoside analog with broad-spectrum antiviral activity of Remdesivir associated with interferon beta (IFN-β) to Lopinavir/Ritonavir and IFN-β [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study included the largest number of patients and recently concluded studies when compared with previous meta-analyses. 23 , 33 , 37 All findings were based on the analysis of RCTs and heterogeneity was low or absent across studies for all outcomes of interest, except for adverse events. However, this study also has a major limitation.…”
Section: Discussionmentioning
confidence: 99%
“…PICOS (participants, interventions, comparison, outcomes, and study design) ( Gebrie et al, 2020 ) was used to formulate the eligibility criteria. - Population: individuals with HIV.…”
Section: Methodsmentioning
confidence: 99%